Pengembangan Lembar Kerja Peserta Didik (LKPD) Media Blended Learning Bermuatan Karakter Baik dan Kuat (Baku) - Hasanah, Salati Asma; Muhyani; Albahar, Rheenda K. (Jurnal PGSD, 2023)
The purpose of this study is to develop LKPD Media Blended Learning contains Good and Strong characters. Good characters indicated by Sincere, Honest, Trusted, Humble" and "Strong characters" indicated by Discipline, Courageous, Tough", as an innovation in Blended Learning media and to straighten up the quality of outcomes and student learning process with Islamic personality. This research was conducted at MI Nurul Yaqin, Cibinong Regency, Bogor. The research method used is Research and Development (R&D) while the development process is adjusted to the research focus which consists of defining, designing and developing. The data obtained is in the form of qualitative. The results of the LKPD research are made in print and also online, i.e. e-learning in pdf form and learning videos, so that students can study at home via cellphones. In learning activities it can be implemented that good character requires three prerequisites, namely: (1) Honest, (2) Fair, and (3) Trust. Strong Character. Strong character demands three prerequisites as well: (1) Courage, (2) Discipline, and (3) Consistent. LKPD media is suitable for implementation as a Blended Learning medium because it is a combination of aspects of internet-based learning with face-to-face learning.